Impact of long working hours on depressive symptoms among COVID-19 frontline medical staff: The mediation of job burnout and the moderation of family and organizational support - Yin, Chengjie; Ji, Jingya; Cao, Xin; Jin, Hui; Ma, Qiang; Gao, Yuexia (Frontiers in Psychology, 2023)
Background: During the COVID-19 pandemic, the frontline medical staff faced more workload and heavier physical and mental stress, which increased their job burnout and negative emotions. However, little is known about the potential factors mediating and moderating these relations. This study investigates the association between long working hours and depressive symptoms among frontline medical staff in China, and explores the potential mediating effect of job burnout, and moderating effect of family and organizational support on these associations. Methods: Data of 992 frontline medical staff who participated in the prevention and control of COVID-19 was obtained from the online survey conducted in November to December 2021 in China. Depressive symptoms were evaluated using the Patient Health Questionaire-9 (PHQ-9). Moderated mediating model was employed to understand the relationship between long working hours (X), depressive symptoms (Y) mediated through job burnout (M), moderated by family support (W1) and organizational support (W2), while controlling all possible covariates. Results: 56.96% of participants worked more than 8 hours per day. 49.8% of them had depressive symptoms (PHQ-9≥5) and 65.8% experienced job-related burnout. Long working hours was positively associated with depressive symptoms score (β = 0.26, 95%CI:0.13 0.40). Mediation analyses revealed that job burnout significantly mediated this relationship (indirect effect = 0.17, 95%CI: 0.08 0.26). Moderated mediation further indicated that both two interactions of social support (family support W1, organizational support W2) and job burnout were negatively related to depressive symptoms among frontline medical staff, indicating that higher social support being less job burnout with lower depressive symptoms. Conclusion: Longer working hours and higher job burnout may contribute to worse mental health among frontline medical staff. Social support could buffer the detrimental effects by reducing their job burnout. Contribution: The main contribution of this study was to estimate the negative effect of long working hours on depressive symptoms among frontline medical staff and explore the potential mediating role of job burnout and moderating role of social support on these associations.